Comparative genomics-based development of a LAMP assay for rapid and reliable in-field detection of Fusarium oxysporum f. sp. cubense tropical race 4 - Mikel Arrieta Salgado; Diane Mostert; Sebastien Ravel; Samuel Rozsasi; Véronique Maillot-Lebon; Agus Sutanto; Catur Hermanto; Mouzdalifa Mmadi; Abdou Azali Hamza; Nadia Adjanoh-Lubin; Babitha Fenelon; Henri Adreit; et al. (PLoS ONE, 2026)
Fusarium wilt, caused by the soilborne fungus Fusarium oxysporum f. sp. cubense (Foc) Tropical race 4 (TR4) is currently devastating Cavendish banana production worldwide. The availability of accurate and rapid field-deployable detection tools is vital for effective disease prevention and containment practices, as no effective treatment is currently available. Design of reliable molecular detection tools, however, is challenged by genetic similarity between non-pathogenic and target Foc strains that are present in symptomatic plant material. The high genetic diversity present among Foc isolates further complicates the identification of unique genomic regions suitable for diagnosis. Current molecular assays are also still mostly confined to laboratory settings and rely on expensive equipment that needs skilled operators to perform. In the present study, a simple loop-mediated isothermal amplification (LAMP) detection assay was developed for direct in-field detection. A comprehensive database of Foc genomes including 148 TR4 genomes and 146 non-target genomes was used, considering the wide diversity within Foc. These genomic sequences were exploited in a comparative genomics in silico pipeline using the KEC method (K-mer elimination by cross-reference), combined with filtering steps using BLASTn, and Illumina read alignments. The specificity of the LAMP primers was validated using a diverse collection of 161 isolates, which included Foc-TR4 isolates, Foc VCGs, F. oxysporum spp. endophytes, other Fusarium spp., and genera which are commonly isolated from banana vascular tissue. The limit of detection reached 10 2 copies µL -1 of plasmid DNA, and the target pathogen was successfully identified both from artificially inoculated and naturally infested material in contrasted environments, indicating the LAMP assay to be a robust and reliable tool fully suitable for field diagnosis.